Economic Analysis Of Super Philip Variety Red Onion Farming In Kediri District, West Lombok Regency - Wati, Hartini; Anwar, Khairil; Mappanganro, Nurlailah (Management Science Doctoral Program, Pasundan University, 2024)
The research was conducted in Kediri District, West Lombok Regency with the aim of finding out the costs, revenues and income of farmers and the economic feasibility of farming the Super Philip variety of shallots as well as analyzing the obstacles in developing the Super Philip variety of shallot farming. The number of respondents was 30 farmers. The data analysis included cost analysis, revenue analysis, income analysis and economic feasibility analysis of Super Philip variety shallot farming. The results show that the production costs of Super Philip variety red onion farming are Rp. 11,593,136 per area of cultivated land while the production cost per ha is IDR 40,965,141. total receipts of Rp. 17,070,300 per area of cultivated land while the total revenue per ha is Rp. 60,318,000 and total income of Rp. 5,477,164 per area of cultivated land while the total income per ha is Rp. 19,352,859 and feasibility analysis using BCR with a result of 1.47. Meanwhile, the obstacles faced in farming the Super Philip variety of shallots consist of seed availability, limited capital, pests and diseases in the Super Philip variety of shallot plants.